2015
DOI: 10.1038/pr.2015.258
|View full text |Cite
|
Sign up to set email alerts
|

Serum hepcidin in infants born after 32 to 37 wk of gestational age

Abstract: Background: Preterm infants are at risk of iron deficiency (ID). Hepcidin has been suggested as a good additional indicator of ID in preterm infants, next to ferritin. Methods: In a prospective observational study, we analyzed serum hepcidin in 111 infants born after 32+0 to 36+6 wk gestational age during the first 4 mo of life. results: Hepcidin concentrations decreased during the first 4 mo of life, and concentrations were lower in infants with ID compared to those without ID. Infants who developed ID at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…TSAT alterations were largely driven by alterations in serum iron rather than by changes to the chaperone protein transferrin, as total iron binding capacity (TIBC) remained relatively constant, though showing a slight fall by 72–96 h of age. Geometric mean hepcidin levels in cord blood (43.8 ng/ml, CI 36.8–52.3 ng/ml) were within the expected reference range for healthy older children 1214 , and had almost doubled by the first post-natal blood draw at a median time of 6 h post-partum (79.4 ng/ml, CI 68.1–92.4). This was followed by a decline at the subsequent sampling point at 24–48 h (45 ng/ml, CI 36.5–57.8) and a rise again by 72–96 h (87.1 ng/ml, CI 73.8–102.7).…”
Section: Resultsmentioning
confidence: 64%
“…TSAT alterations were largely driven by alterations in serum iron rather than by changes to the chaperone protein transferrin, as total iron binding capacity (TIBC) remained relatively constant, though showing a slight fall by 72–96 h of age. Geometric mean hepcidin levels in cord blood (43.8 ng/ml, CI 36.8–52.3 ng/ml) were within the expected reference range for healthy older children 1214 , and had almost doubled by the first post-natal blood draw at a median time of 6 h post-partum (79.4 ng/ml, CI 68.1–92.4). This was followed by a decline at the subsequent sampling point at 24–48 h (45 ng/ml, CI 36.5–57.8) and a rise again by 72–96 h (87.1 ng/ml, CI 73.8–102.7).…”
Section: Resultsmentioning
confidence: 64%
“…(A) Full-term neonates: α shows the weighted mean (95% CI) for all studies seen in Supplemental Figure 1A; β, χ, and ε show Prentice et al ( 99 ); δ shows Kulik-Rechberger et al ( 46 ). (B) Preterm neonates: α shows the weighted mean (95% CI) for all studies seen in Supplemental Figure 1B; β shows Uijterschout et al ( 100 ).…”
Section: Resultsmentioning
confidence: 99%
“…Lower hepatic expression of hepcidin was also reported in naturally fed piglets compared with those fed iron-supplemented formula [19]. A study in former preterm infants at 4 months of age observed lower serum hepcidin levels in those fed breast milk compared with those predominantly fed formula [20].…”
Section: Discussionmentioning
confidence: 96%